A proteomic landscape of pharmacologic perturbations for functional relevance - Zhiwei Liu; Shangwen Jiang; Bingbing Hao; Shuyu Xie; Yingluo Liu; Yuqi Huang; Heng Xu; Cheng Luo; Min Huang; Minjia Tan; Jun-Yu Xu (Elsevier, 2024)
Pharmacological perturbation studies based on protein-level signatures are fundamental for drug discovery. In the present study, we used a mass spectrometry (MS)-based proteomic platform to profile the whole proteome of the breast cancer MCF7 cell line under stress induced by 78 bioactive compounds. The integrated analysis of perturbed signal abundance revealed the connectivity between phenotypic behaviors and molecular features in cancer cells. Our data showed functional relevance in exploring the novel pharmacological activity of phenolic xanthohumol, as well as the noncanonical targets of clinically approved tamoxifen, lovastatin, and their derivatives. Furthermore, the rational design of synergistic inhibition using a combination of histone methyltransferase and topoisomerase was identified based on their complementary drug fingerprints. This study provides rich resources for the proteomic landscape of drug responses for precision therapeutic medicine.